2017
DOI: 10.4103/ijciis.ijciis_8_17
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic tension pneumocephalus – Two cases and comprehensive review of literature

Abstract: Although traumatic pneumocephalus is not uncommon, it rarely evolves into tension pneumocephalus (TP). Characterized by the presence of increasing amounts of intracranial air and concurrent appearance or worsening neurological symptoms, TP can be devastating if not recognized and treated promptly. We present two cases of traumatic TP and a concise review of literature on this topic. Two cases of traumatic TP are presented. In addition, a literature search revealed 20 additional cases, of which 18 had sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 34 publications
(60 reference statements)
1
66
1
Order By: Relevance
“…The most common etiology by far was trauma. Similar to our case, Pillai et al [5] reported that frontal bone/sinus fracture is the most common injury associated with traumatic TP. Nineteen cases were picked up by CAT scans and one by MRI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The most common etiology by far was trauma. Similar to our case, Pillai et al [5] reported that frontal bone/sinus fracture is the most common injury associated with traumatic TP. Nineteen cases were picked up by CAT scans and one by MRI.…”
Section: Discussionsupporting
confidence: 90%
“…Pillai et al [5] conducted a comprehensive review of all reported cases of traumatic TP in the literature and identified 20 of such cases. In their review, there were 17 males and three females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The best way to diagnose this complication by CT scan of the brain is without injecting. Treatment includes craniotomy, extra air discharge in the brain, finding the location of air penetration (depending on the type of surgery), choosing air with water, and using intracranial controlling drugs (9).…”
Section: Discussionmentioning
confidence: 99%